Family Chagas disease. A Case with Acute Lung Edema and Case Possibly Congenital Chagas Disease - Peralta V., Aurelio (1961)
From June 1960 to June 1961, using our "index of suspicion" 1 in the Department of Cardiology, Hospital Police Lima, we diagnosed 5 cases over Chagas disease originating in tacan, the first of Sagollo two (Locumba) and the last three of Tala (Tarata).